1993
DOI: 10.1007/bf00171743
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for intussusceptive capillary growth in the chicken chorio-allantoic membrane (CAM)

Abstract: The aim of our investigations was to test whether the chicken chorio-allantoic membrane (CAM) could be an adequate in vivo model for a new mode of capillary growth, originally described in the rat lung and termed intussusceptive microvascular growth. According to that concept the capillary system does not grow by sprouting of vessels, but expands by insertion of transcapillary tissue pillars or posts which form new intercapillary meshes. In the present study, we observed slender transcapillary tissue pillars w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 24 publications
8
80
0
1
Order By: Relevance
“…It is thought that the pillars then increase in diameter and become a capillary mesh. Patan et al (1993) observed the same morphological transformation during IMG in the CAM (Fig. 1).…”
Section: New Model Of Cam Vascular Growth: the Intussusceptive Modesupporting
confidence: 65%
“…It is thought that the pillars then increase in diameter and become a capillary mesh. Patan et al (1993) observed the same morphological transformation during IMG in the CAM (Fig. 1).…”
Section: New Model Of Cam Vascular Growth: the Intussusceptive Modesupporting
confidence: 65%
“…Observations made both in the lung and in the chorioallantoic membrane (CAM) of the chicken revealed some additional modes of transluminal pillar formation (Patan et al, 1993(Patan et al, , 1997. These variants are schematically represented in Figure 5, which illustrates the various ways by which transluminal pillars can be formed.…”
Section: Alternative Modes Of Transcapillary Pillar Formationmentioning
confidence: 99%
“…Therefore, we turned to the in vivo model of the shell-free chicken culture technique established by Auerbach and coworkers (1974). With this approach, it was repeatedly possible to demonstrate the in vivo appearance of transcapillary pillars within relatively short periods of observation (Patan et al, 1993;Kö nig et al, 1997).…”
mentioning
confidence: 99%
“…Tissue pillars formed in this manner lead, in the first instance, to rapid expansion of the primary capillary plexus: intussusceptive microvascular growth (IMG, Burri and Tarek, 1990;Patan et al, 1993;Schlatter et al., 1997); and then to the formation of arterial and venous feeding vessels: intussusceptive arborization (IAR, Djonov et al, 2000a,b). In addition, as we describe in the present study, intussusceptive processes occur also in vessels of larger diameter and contribute to remodeling and pruning at points of bifurcation: intussusceptive branching remodeling (IBR).…”
Section: Demonstration Of Intussusceptive Branching Remodeling In Thementioning
confidence: 99%
“…It originates from fusion of the angiogenic mesodermal allantois with the ectodermal chorion and, thus, corresponds to the placenta of mammals. In the CAM, intussusceptive microvascular growth (IMG; Caduff et al, 1986;Burri and Tarek, 1990) expands the capillary plexus (Patan et al, 1993;Schlatter et al, 1997) from which arterial and venous feeding vessels emerge by means of intussusceptive arborization (IAR) (Djonov et al, 2000a,b). The vascular bed of the CAM expands at an extraordinary speed for approximately 1 week by means of IMG and endothelial proliferation in capillaries, the later process ceasing at around incubation day 12 (E12) (Kurz et al, 1995).…”
Section: Introductionmentioning
confidence: 99%